Studies in International Relations and Politics : New Europe and Beyond. - Bagatelas, William T. (Budrich UniPress, Limited, 2010)
The book represents a major examination regarding the current practice of international relations and world politics. It analyzes the international relations of large, medium, and smaller sized actors, and how they influence the larger dynamics and ebb and flow of the international system. While assessing the perspectives of 21st century international systems, it also examines how relations between actors may improve or worsen, surely the most timely issue presently facing global and relational politics. Through globalization, the concept of a more balanced version of the American Dream has extended worldwide. Irrespective of wealth or poverty, globalization's promise of prosperity has been adopted eagerly, despite uneven progress along the way. Together with the larger realities of Neo-Liberal thinking and influence, where global and cyber markets have evolved with little supervision, we have seen a move from enlightened self interest to the reality of pure self-interest. This book addresses the larger ethical implications of this global trend.